Nutritional composition, antioxidant activities, and antiulcer potential of lentinus squarrosulus(Mont.) mycelia extract - Omar, N.A.M.; Abdullah, N.; Kuppusamy, Umah Rani; Abdulla, M.A.; Sabaratnam, V. (Hindawi, 2011)
Water extract of Lentinus squarrosulus mycelia was analysed for nutritional content, antioxidant capacity, and antiulcer ability. The extract contains high protein (57.6 g/100 g) and low total fat (0.5 g/100 g) and is rich in magnesium (0.4 g/100 g), potassium (3.8 g/100 g), vitamins B1 (1.42mg/100 g), and B3 (194.29 mg/100 g) with total phenolic content of 39.16 mg/100 g. The cupric reducing antioxidant capacity and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity of the extract were A(450) of 0.20 perpendicular to 0.03 at 0.5mg/ml and IC(50) of 14.29 mg/ml, respectively. Oral feeding of L. squarrosulus extract (250 mg/kg) offered significant gastric mucosal protection of Sprague-Dawley rats compared to cimetidine (50 mg/kg). The ulcer healing rate of ulcerated rats after 24, 48, and 72 hours of treatment was 82, 90, and 100, respectively. The IL-1 beta level in the serum and the NF-kappa B level in the tissues indicate that the healing potential was associated with attenuation of proinflammatory cytokines.